Especificação e implementação de uma linguagem para transformação de modelos MOF em repositórios dMOF - Lins, Hertz Wilton de Castro (2006)
This work presents the specification and the implementation of a language of Transformations in definite Models specification MOF (Meta Object Facility) of OMG (Object Management Group). The specification uses a boarding based on rules ECA (Event-Condition-Action) and was made on the basis of a set of scenes of use previously defined. The Parser Responsible parser for guaranteeing that the syntactic structure of the language is correct was constructed with the tool JavaCC (Java Compiler Compiler) and the description of the syntax of the language was made with EBNF (Extended Backus-Naur Form). The implementation is divided in three parts: the creation of the interpretative program properly said in Java, the creation of an executor of the actions specified in the language and its integration with the type of considered repository (generated for tool DSTC dMOF). A final prototype was developed and tested in the scenes previously defined